Maternal Undernutrition and Low Birth Weight in a Tertiary Hospital in Sudan: A Cross-Sectional Study - Bilal, Jalal A.; Rayis, Duria A.; AlEed, Ashwaq; Al-Nafeesah, Abdullah; Adam, Ishag (Frontiers in Pediatrics, 2022)
Background: The World Health Organization set a Global Nutrition Target of a 30% reduction in LBW by 2025. Maternal malnutrition/undernutrition is among the most important modifiable risk factors for impaired fetal growth. This study investigates the effect of maternal undernutrition on LBW in Sudan. Methods: A cross-sectional study was conducted at Saad Abuelela Hospital in Khartoum, Sudan, from May to October 2020. The sociodemographic and obstetric data of the women were gathered via questionnaire, and their mid-upper arm circumference (MUAC) was measured. Maternal undernutrition was defined as a MUAC of <23 cm. Results: In total, 1,505 pairs of pregnant women and their newborns were enrolled in the study. The medians [interquartile (IQR)] of the age, parity, and gestational age were 27.0 (9.0) years, 1.0 (3.0), and 38.0 (2.0) weeks, respectively. The median (IQR) of the birth weight was 3,028.0 (690.0) g. Of the 1,505 participants, 182 (12.1%) delivered LBW infants. Multivariate logistic regression showed that MUAC [Adjusted odds ratio (AOR) = 0.91, 95% confidence interval (CI) = 0.87‒0.96] and gestational age (AOR = 0.79, 95% CI = 0.73‒0.85) were negatively associated with LBW. The level of antenatal care ˂ 2 visits (AOR = 2.10, 95% CI = 1.30‒3.57) was associated with LBW. Women with undernutrition were at a higher risk of delivering LBW infants (AOR = 1.66, 95% CI = 1.09‒2.53). Conclusion: LBW is a health problem in Sudan, and women with undernutrition were at a higher risk of delivering LBW infants.